The limitations of using only CAD and DHM in design relating to high value manufacturing - Johnson, Teegan L.; Fletcher, Sarah R. (Taylor & Francis, 2015)
The ergonomics suites available within computer aided design and digital human modelling programs are increasingly being used to predict and prevent ergonomic and human factors risk due to poor design. To further aid the reduction in poor design, it is of importance to understand the need for user input and the limitations of these software programs. These limitations include: the small number of available anthropometric population samples; and the disconnect between what a designer perceives as possible, and what is possible within a manufacturing environment. A method of mitigating these limitations is the use of user input using virtual reality suites, mock-ups and motion capture technology.